EFL LEARNERS’ MORPHOLOGICAL AWARENESS AND LEXICAL KNOWLEDGE (A CORRELATIONAL STUDY) - Muhammad Andrean Syahsurya (EDUCAFL : Journal of Education of English as Foreign Language, 2022)
Lexis or vocabulary is one of the important components of the language. Without knowing the vocabulary, learners of a language cannot be able to understand the language itself because vocabulary establishes the frame of language. It is important for learners to enhance their lexical knowledge. Morphological awareness has significant role on the lexical knowledge. This study aims to find out the correlation between morphological awareness and lexical knowledge among Indonesian EFL learners who possess Indonesian language as their first language. Indonesian is an agglutinative language which relies much on prefix and suffix. This study employs quantitative approach with correlation statistics design. The participants of this study are 89 first-year students of English Language Education Program Universitas Brawijaya. The findings revealed that the majority of the participants are in the medium level of morphological awareness and lexical knowledge. The findings show that there is a significant correlation between morphological awareness and lexical knowledge with .842 correlation degrees. Learners with high morphological awareness will have high lexical knowledge. The relationship applies in Indonesian EFL learners who possess Indonesian language as their first language that belongs to agglutinative language which contains several morphemes per word. It is suggested for the future researchers to look greater depth into morphological awareness and lexical knowledge in causal relationship.